TEMBANG “LIR-ILIR” BAGI GURU GUNA MENUMBUHKAN MOTIVASI BELAJAR DI PENDIDIKAN FORMAL (STUDI KASUS DI TK WAHID HASYIM DINOYO MALANG) - Pujiharti, Endang Sih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Motivation to learn in early childhood are things that need attention from parents, teachers and the community, because it is generally a child is still not able to realize the wishes and needs related to learning without the help of others. Song